(untitled) (Academicia Globe: Inderscience Research, 2025)
This article analyzes foreign experience in implementing tax administration for large taxpayers, and as a result of these analyses, issues of improving the tax legislation of the Republic of Uzbekistan, proposals and recommendations for further improving the tax administration of large taxpayers were developed.